Ultra-fast Broadband: The New Zealand Experience - Milner, Murray Owen (Journal of Telecommunications and the Digital Economy, 2020)
This paper outlines the key learnings from the first decade of the Ultra-fast Broadband (UFB) and its associated Rural Broadband initiatives (RBI) in New Zealand. The UFB initiative provides the opportunity for 87% of New Zealand premises to have access to broadband using Fibre to the Premises (FTTP) technology. The remaining 13% of premises have access to enhanced wireless broadband. These initiatives are due for completion by year end 2023 and are showing promising results as at the end of 2019. The success of these initiatives has not been achieved without a lot of challenges along the journey. However, as it is shown in the paper, the alignment of policy around broadband development across government and the establishment of a set of policy objectives and principles at the outset has enabled the initiatives to stay on track over time, relative to the original intentions. The establishment of these policy principles and the strict adherence to these principles throughout the execution of the initiatives has been the most significant learning from this substantial programme of telecommunications development in New Zealand.